Quantitative electroencephalography as a marker of cognitive fluctuations in dementia with Lewy bodies and an aid to differential diagnosis. Issue 6 (June 2018) - Stylianou, Myrto; Murphy, Nicholas; Peraza, Luis R.; Graziadio, Sara; Cromarty, Ruth; Killen, Alison; O' Brien, John T.; Thomas, Alan J.; LeBeau, Fiona E.N.; Taylor, John-Paul
Highlights: EEG slowing was evident in dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) and less in Alzheimer's disease (AD) patients compared to controls. Dominant rhythm variability was larger in AD but only correlated with cognitive fluctuations in DLB. QEEG variables classified DLB and AD patients with high sensitivity and specificity. Abstract: Objective: We investigated for quantitative EEG (QEEG) differences between Alzheimer's disease (AD), dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) patients and healthy controls, and for QEEG signatures of cognitive fluctuations (CFs) in DLB. Methods: We analysed eyes-closed, resting state EEGs from 18 AD, 17 DLB and 17 PDD patients with mild dementia, and 21 age-matched controls. Measures included spectral power, dominant frequency (DF), frequency prevalence (FP), and temporal DF variability (DFV), within defined EEG frequency bands and cortical regions. Results: DLB and PDD patients showed a leftward shift in the power spectrum and DF. AD patients showed greater DFV compared to the other groups. In DLB patients only, greater DFV and EEG slowing were correlated with CFs, measured by the clinician assessment of fluctuations (CAF) scale. The diagnostic accuracy of the QEEG measures was 94% (90.4–97.9%), with 92.26% (80.4–100%) sensitivity and 83.3% (73.6–93%) specificity. Conclusion: Although greater DFV was only shown in the AD group, within the DLB group a positive DFV – CF correlation was found. QEEG measures could classify DLB and AD patients with high sensitivity and specificity. Significance: The findings add to an expanding literature suggesting that EEG is a viable diagnostic and symptom biomarker in dementia, particularly DLB.